Synthesis, Crystal Structure, and Luminescent Property of One 3D Pillared-Layer Complex Based on 5-Methoxyisophthalate and 1, 4-Bis(imidazol-1-yl)-butane Ligands. Issue 4 (2nd April 2016) - Wang, Hua-Rui; Wang, Jian-Ge
Abstract : One three-dimensional (3D) coordination polymer, [Zn(L)(bimb)0.5 ] n (1 ) (L = 5-methoxyisophthalate, bimb = 1, 4-bis(imidazol-1-yl)-butane), was synthesized and studied by elemental analysis, IR spectroscopy, and X-ray crystallography. This complex belongs to monoclinic system with space group P 21 / n, and exhibits a 3D (3, 4)-connected net. In the structure of1, the L ligand connects Zn(II) ions giving rise to a 2D helical layer. Adjacent ones are joined by bimb pillars to generate a novel 3D pillared-layer framework. Furthermore, luminescent property of1 was also investigated.